Perspectives on modern South Asia : a reader in culture, history, and representation - Visweswaran, Kamala (Malden : Wiley-Blackwell, 2011)
'Perspectives on Modern South Asia presents an exciting core collection of essays drawn from anthropology, literary and cultural studies, history, sociology, economics, and political science to reveal the complexities of a region that is home to a fifth of humanity. Presents an interdisciplinary overview of the origins and development of the eight nations comprising modern South Asia: Afghanistan, Bhutan, Bangladesh, India, the Maldives, India, Pakistan, and Sri Lanka. Explores South Asia's common cultures, languages and religions and their relationship to its ethnic and national differences. Features essays that provide understandings of the central dynamics of South Asia as an important cultural, political, and economic region of the world.'--
'While the eight South Asian countries of Afghanistan, Bhutan, Bangladesh, India, the Maldives, India, Pakistan, and Sri Lanka continue to be divided by deep national differences, they also share common cultures, languages, and religions. Perspectives on Modern South Asia is an interdisciplinary collection of readings drawn from anthropology, literary and cultural studies, history, sociology, economics, and political science that will shape a fuller understanding of the complexities of contemporary South Asia. Featuring selections from an international group of experts, this volume explores the tension between the lived experience of cultural or religious tolerance and the deployment of culture or religion for nationalist purposes. Visweswaran offers a wealth of thought-provoking insights into the origins and development of the shifting politics, cultures, economies, and national identities of a region of the world that is home to a fifth of humanity'--
Includes bibliographical references and index.
Keywords: Group identity -- South Asia; Ethnicity -- South Asia; South Asia -- Civilization; South Asia -- Social conditions